2010
DOI: 10.1002/jcb.22761
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins from the American Cranberry (Vaccinium macrocarpon) inhibit matrix metalloproteinase‐2 and matrix metalloproteinase‐9 activity in human prostate cancer cells via alterations in multiple cellular signalling pathways

Abstract: Prostate cancer is one of the most common cancers in the Western world, and it is believed that an individual's diet affects his risk of developing cancer. There has been an interest in examining phytochemicals, the secondary metabolites of plants, in order to determine their potential anti-cancer activities in vitro and in vivo. In this study we document the effects of proanthocyanidins (PACs) from the American Cranberry (Vaccinium macrocarpon) on matrix metalloproteinase (MMP) activity in DU145 human prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…Studies on the possible effects of cranberry and its components on prostate cancer were realized only in DU 145 human prostate cancer cells which are androgen independent. Treatment of cranberry proanthocyanidinenriched fraction inhibited matrix metalloproteinase-2 and -9 (MMP) activity through the induction and/or inhibition of specific temporal MMP regulators 10 . MMP activity is associated with tumor cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the possible effects of cranberry and its components on prostate cancer were realized only in DU 145 human prostate cancer cells which are androgen independent. Treatment of cranberry proanthocyanidinenriched fraction inhibited matrix metalloproteinase-2 and -9 (MMP) activity through the induction and/or inhibition of specific temporal MMP regulators 10 . MMP activity is associated with tumor cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These include vitamins C, E, K, organic and phenolic acids, saccharides, flavan-3-ols, flavonols, anthocyanins, anthocyanidins, proanthocyanidins and triterpenoids, shown to possess anti-bacterial, anti-viral, anti-oxidant, anti-inflammatory, anti-angiogenic and anti-cancer activities 8,9 . Most of this evidence, with the exception of preventing urinary tract infections, was derived from studies on prostate cancer cell lines [10][11][12][13] . Our recent clinical study reported that daily intake of 1500 mg cranberry powder for 6 months significantly reduced total prostate-specific antigen (PSA) elevated from chronic non-bacterial prostatitis, and/or benign prostate hyperplasia 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The data presented in this review strongly support the anti-proliferative and pro-death capacities of cranberries in a multitude of cancer cell lines and select in vivo models including xenograft and chemically induced cancer models. The precise cancer inhibitory mechanisms associated with cranberries in specific targets are still be elucidated, but preclinical studies utilizing cranberry proanthocyanidins show inactivation of the PI3K/AKT/mTOR pathways and modulation of MAPK signaling in esophageal, neuroblastoma, ovarian and prostate cancer cells and in esophageal xenografts [39,44,49,52]. Moreover, cranberry proanthocyanidins have recently been shown to induce autophagic markers in vitro and in vivo [39], suggesting an alternative mode of cell death induction and tumor inhibition that requires further evaluation in additional cancer targets.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cell lines originating from the oral cavity are susceptible to reduced viability following treatment with cranberry extract (50.0-180.6 µg/mL), cranberry juice extract (150.0 µg/mL) and a total polyphenolic fraction (200.0 µg/mL) with cranberry extract (50.0 µg/mL) treatment of CAL27 cells having the lowest GI 50 [24,33,47]. Ten studies have documented the effectiveness of a cranberry extract, cranberry juice extract, a flavonoid rich extract and cranberry proanthocyanidins at significantly reducing the viability of prostate cancer cells [24][25][26]28,33,36,45,[50][51][52]. The most efficacious constituent appears to be a cranberry proanthocyanidin extract, which inhibits the viability of RWPE-1 and RWPE-2 prostate cancer cell lines with a GI 50 of approximately 6.5 µg/mL [33].…”
Section: Cjementioning
confidence: 99%
“…Furthermore, cranberry proanthocyanidins (25.0 µg/mL) increase mitogen-activated protein kinase (MAPK) signaling and decrease PI3K/AKT signaling in prostate cancer cells, suggesting a common cell death mechanism with esophageal adenocarcinoma, ovarian and neuroblastoma cancer cells [52].…”
Section: Cranberry Derived Extracts and Constituents Induce Cell Deatmentioning
confidence: 99%